The Chinese Revolution. (World Book's documenting history, 2011)
"A history of the Communist revolution in China, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.